Learning oral presentation skills "why not learn collaboratively and innovatively": a handbook / Juritah Misman - Misman, Juritah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Current employment scenario requires undergraduates to have good abilities to engage in communication and presentation skills. Usual practices in the oral communication classrooms are by learners learning more about the strategies and skills of effective oral presentation skills through lectures, textbooks, sample video presentations and others. So, what if students become independent learners and they can learn, develop and practice their presentation skills in or outside the classrooms with their peers using some useful, innovative strategies and technology suggested in this handbook. This handbook also reviews some of the key concepts of rich social support of peer learning and coaching learners' presentation skills and suggests a series of five collaborative activities to help learners to work together in augmenting their oral skills. This innovative booklet appends some learning notes and strategies that could help individuals and learners, specifically to become better, more effective communicators and presenters. This handbook could be potentially commercialized to be developed into multimedia interactive hardware and software in future.